Association between height at age 2 years and adolescence school performance: evidence from Birth to Twenty Cohort Study - Nkomo, Palesa Manthabiseng (My University, 2011)
Background The first two years of a child’s life are crucial for cognitive development. In societies where there are high rates of poverty, children are at risk of undernutrition and subsequently stunting. Insufficient nutrition in early childhood results in growth retardation in young infants and subsequently weak school performance later in life due to poorer cognitive development. As far as we know no study has been conducted in South Africa to examine the association between height at age 2 years and school performance at the end of primary school. Purpose The primary objective of this study was to investigate the association between growth at age 2 years and education performance (school performance in Mathematics and English or first language) of adolescents at the end of primary school (grade 7). In addition, other growth variables such as weight-for-age, BMIfor- age and weight-for-height were tested for the association as a secondary objective. Prevalence of stunting, underweight, wasting and obesity at age two years was also investigated. Methods This study is a primary analysis of historical data collected from Birth to Twenty (BT20) cohort in Johannesburg, South Africa. A cohort study conceptualised to v investigate the effects of the urbanization and societal transition on health and development A longitudinal study design within the BT20 cohort was employed. A total of 252 study participants were included in the study. An ordinal logistic model was used to test for association between growth at age two years and school performance. Potential confounders such as maternal education, birth weight and socio-economic status as defined by household assets were adjusted for in the model. Results At age two years, about 29% of the study participants were stunted as defined by height-for-age, based on the WHO 2006 growth standards. The proportion of girls defined as stunted was equal to that of boys. Levels of underweight, wasting and obesity were 9%, 6% and 2% respectively. The risk of low versus combined high and average performance in Mathematics at grade 7 was about three times more likely in study participants whose heightfor- age was below -3SD and seven times more likely for those below -4SD. Participants whose weight-for-age as defined by the WHO reference was below - 2SD were more than three times more likely to achieve a low score versus a combined high and average score in English or first language. There was no evidence of correlation between low birth weight, wasting and obesity and poor education performance for both Mathematics and English results Conclusion: We conclude that there is an association between height at age 2 years and school performance at the end of primary school.
MSc (Med), Epidemiology and Biostatistics, Faculty of Health Sciences, University of the Witwatersrand
Keywords: school performance; height at age 2; adolescents